Dependence of Cell Survival on Correlative Activities of Xanthine Oxidase and Dihydopyrimidine Dehydrogenase in Human Brain-Derived Cell Culture - E. Danielyan, Kristine (Central Nervous System Agents in Medicinal Chemistry, 2013)
Xanthine Oxidase (XO; EC. 1.1.3.22) and Dihydropyrimidine Dehydrogenase (DPD; EC. 1.3.1.2) are two enzymes responsible for the last steps of purine and pyrimidine catabolism, and hydroxylation of a wide variety of pyrimidine, pterin, and aldehyde substrates. Elion showed that purine isomers can be converted to various nucleotides, which influence pyrimidine metabolism (Elion, 1978). The current study is devoted to delineating the correlation between survival of human brain derived cells in culture and the activities of XO and DPD. Cultivation of (E90) brain cells was performed by the modified method of Mattson (1990). XO activity was measured by the formation of uric acid in the tissue. DPD activity was evaluated by the reduction of NADPH and the associated absorbance decrease at 320 nm. Cell death was detected by Trypan Blue dye leakage. During our investigation, we noticed a reversed correlation between the activities of XO and DPD over 12 days under normal conditions as well as in the presence of the XO and DPD inhibitors, allopurinol and dipyridamole. During the treatment period of 12 days, as well as from days 7-12 with the inhibitors, we observed cell protection, whereas treatment from days 1-7 elevated the percentage of dead cells in culture. A low dosage of allopurinol over 12 days also stimulated cell growth and increased their number in culture. We concluded that timely inhibition of XO as well as DPD activities might initiate cell growth and prevent their death. However, the main influence as the final enzyme of purine metabolism in the processes of cell proliferation belongs to XO in contrast to DPD.
Keywords: brain